A Study on the Effect of Squish Area on Engine Performance of Single Cylinder Natural Gas Converted Engine - Nguyen, Van Tien; Tran, Dang Quoc (JST: Engineering And Technology For Sustainable Development, 2022)
Today, the prices of fossil fuels such as gasoline and diesel are skyrocketing, oil depletion and air pollution are major challenges for us and the auto industry in particular. Natural gas has known as a potential alternative fuel of internal combustion engines because of its advantages such as the research octane number is higher than that of gasoline, the low heat value is higher in comparison with gasoline and diesel, the safety in use. This paper presents a study on the influence of squish area on engine performance of single cylinder natural gas converted engine. The obtained results indicated that the increase of compression ratio only augmented the risk of knocking for single cylinder natural gas converted engine. Conversely, the modification of bowl-in-piston is directly varied squish area, thus the turbulent kinetic energy of the gas flows at the end of the compression stroke increased in comparison with the flat head piston of the original engine.